PO 18122 - Treatment of Charcot arthropathy in the ankle joint - Cursino Fernandes, Milena Peloggia; de Marchi Neto, Noé; Cardenuto Ferreira, Ricardo; Tulio Costa, Marco; Bergamasco, Jordanna; Gobbo, Daiana (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Charcot arthropathy can lead to joint destruction and often causes ulcers at sites of bony prominences. In the ankle, it causes instability that limits gait and makes it difficult for patients to wear shoes or orthoses. This was a retrospective study describing cases of Charcot arthropathy of the ankle treated at our institution from 1997 to 2017. Methods: Over the study period, we treated 252 patients with Charcot arthropathy. Of these patients, 27 presented the disease exclusively in the ankle. The selected cases were unilateral; 17 of the patients were men, and the mean age was 55 years. Nine patients were treated conservatively, and 18 were treated surgically to stabilize the ankle (including the hindfoot, if necessary). During surgery, different fixation methods were used depending on the presence or absence of ulcer at the time of the intervention. At the end of the treatment, we assessed the patient’s ability to wear shoes or orthoses for walking, the stability of the ankle joint and, in surgical cases, union. We considered a good outcome when the patient was able to walk wearing shoes or orthoses, and the limb was stable; an acceptable outcome when the limb was unstable, but the patient adapted to orthoses; and a poor outcome when the patient was unable to walk, and the ankle was unstable or amputated. Results: Nine patients underwent conservative treatment using total contact casting at the initial phase of the disease, followed by orthosis after union. Of these patients, the outcome was poor for 5, good for 3 and acceptable for 1. Eighteen patients underwent reconstructive surgery; 12 patients had a good outcome; 2 patients underwent amputation, and 4 patients had unsuccessful surgeries. Conclusion: Charcot arthropathy of the ankle causes considerable instability. Conservative treatment of the disease fails to provide good outcomes, and the patients who underwent reconstructive surgery had the best functional and clinical evaluations.